Molecular detection of Babesia spp. using PCR on dogs from Bogor and Jakarta, Indonesia - Veerasamy, Suganti; Nugraha, Arifin Budiman; Cahyaningsih, Umi; Fitri, Arni Diana; Satyawardana, Wirokartiko (ARSHI Veterinary Letters, 2024)
Canine babesiosis is caused by Babesia spp. infection; however, detection methods are limited in Indonesia. This study aimed to detect Babesia spp. in dogs from Bogor and Jakarta by PCR. Blood samples (n=56) were collected and examined using blood smears with 10% Giemsa staining and PCR targeting the 18S rRNA gene. Haematological profiles were also analysed. The results showed that 12.5% of mixed-breed dogs from Bogor were positive for Babesia spp. by both methods. Infected dogs exhibited reduced red blood cell counts and increased white blood cell counts, indicating anaemia and an immune response. This study highlights the importance of molecular methods for accurate diagnosis and supports the need for preventive and control programs.